A two year retrospective study of cytohistopathological correlation of cervical smear in a tertiary care hospital - Sirasagi, Anil Kumar; K, Arpitha; Neha, Saara; Pattar, Pratima Manohar (Asian Journal of Medical Sciences, 2021)
Background: Cervical cancer in women is the second most common cancer and the commonest cause of mortality in developing countries. The introduction of Pap smear test changed the scenario of cervical cancer with an intense drop in the incidence and mortality due to invasive cervical cancer. Aims and Objective: To evaluate the patterns of cervical smear cytology and to correlate the cervical smear diagnosis with histopathological diagnosis and to assess the efficacy of Pap smears in diagnosing cervical lesions. Materials and Methods: This two-year retrospective study (January 2018 to December 2019) was done in the department of Pathology in a tertiary care hospital. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated considering histopathological diagnosis of cervical biopsy as the gold standard. Results: A total of 316 Pap smears were studied, out of which we selected 154 cases who also undergone biopsy or hysterectomy. Epithelial cell abnormalities (ECA) were found in 28 cases (18.2%). Among this the most common ECA was Atypical squamous cells of undetermined significance (ASCUS) seen in 10 cases (6.5%) followed by LSIL (5.2%), HSIL (3.2%) and SCC of cervix (3.2%). The overall correlation between cervical cytology and histopathology was found in 125 out of 154 cases (81.16%). The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of pap smear was 90.57%, 62.50%, 95.41%, 43.47% and 87.66% respectively. Conclusion: Pap smear is a simple, safe, non-invasive and effective method for detection of lesions of the cervix and ECA. Hence, better awareness and periodical cytological screening programs can help in the early detection of malignant cervical lesions and thereby reducing the morbidity and mortality related to this malignancy.